The Role Of Brand Love As A Mediation Of Satisfaction And Loyalty - Hayuningtias, Kristina Anindita; Basiya, Robertus; Putra, Harmanda Berima (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2023)
This study aims to analyze the role of brand love in the relationship between satisfaction and loyalty. The sample size in this study was 174 respondents who were consumers of skin care products . Based on the results of data analysis using Structural Equation Modeling (SEM), it was found that satisfaction has a positive effect on brand love. Still, satisfaction has yet to be proven to affect consumer loyalty. Meanwhile, brand love proves to have a positive influence on loyalty. Furthermore, brand love does not mediate the relationship between satisfaction and loyalty. Key Words: satisfaction, brand love, loyalty.